Penetratin and derivatives acting as antifungal agents - Masman, Marcelo Fabricio (2009)
The synthesis, in vitro evaluation, and conformational study of RQIKIWFQNRRMKWKK-NH2 (penetratin) and related derivatives acting as antifungal agents are reported. Penetratin and some of its derivatives displayed antifungal activity against the human opportunistic pathogenic standardized ATCC strains Candida albicans and Cryptococcus neoformans as well as clinical isolates of C. neoformans. Among the compounds tested, penetratin along with the nonapeptide RKWRRKWKK-NH2 and the tetrapeptide RQKK-NH2 exhibited significant antifungal activities against the Cryptococcus species. A comprehensive conformational analysis on the peptides reported here using three different approaches, molecular mechanics, simulated annealing and molecular dynamics simulations, was carried out. The experimental and theoretical results allow us to identify a topographical template which may provide a guide for the design of new compounds with antifungal characteristics against C. neoformans.